2019
DOI: 10.1186/s41240-019-0116-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of arsenic on growth, hematological parameters, and plasma components of starry flounder, Platichthys stellatus, at two water temperature conditions

Abstract: The purpose of this study is to investigate the changes in growth, hematological parameters, and plasma components of juvenile starry flounder, Platichthys stellatus, following exposure to varying arsenic concentrations present at different water temperatures. P. stellatus (total length, 15.9 ± 0.4 cm; body weight, 62.2 ± 4.2 g) were exposed for 4 weeks to waterborne arsenic (sodium arsenite, As) at 0, 150, 300, and 600 μg/L at temperatures of 12°C and 18°C. Toxic effects of As exposure on P. stellatus were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Eleven heavy metals were monitored in the pre-to-post lockdown including the four critically categorized four heavy metals such as arsenic (As), cadmium (Cd), chromium (Cr), and lead (Pb) (Kaur et al 2011 ; Han et al 2019 ; Rahman and Singh 2019 ). The lead concentration decreased significantly in the recent assessments when compared with pre-lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven heavy metals were monitored in the pre-to-post lockdown including the four critically categorized four heavy metals such as arsenic (As), cadmium (Cd), chromium (Cr), and lead (Pb) (Kaur et al 2011 ; Han et al 2019 ; Rahman and Singh 2019 ). The lead concentration decreased significantly in the recent assessments when compared with pre-lockdown.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, Oluwatosin et al [15] reported that the sub-lethal exposure showed reduction in growth with an increase in PbCl 2 concentration and the specific growth rate in the control was higher than other treatments with PbCl 2 . In another development, Han et al [16] found that growth and hematological parameters determined decreased with increasing arsenic concentration, while the concentration of plasma components measured increased. Also, fish exposed to 10, 50 and 100µgHg/L showed a significant decrease in growth rates as from days 14 to 35 [17] .…”
Section: Length-weight Relatioships Of Clarias Gariepinus Exposed To Sub-lethal Concentrations Of Pb Toxicant For a Period Of 12 Weeksmentioning
confidence: 97%
“…Continuous exposure of less than one-week-old guppy (Poecilia reticulata) to phthalate for 14-91 days reduced body weight and body length (131). In juvenile starry flounder (Platichthys stellatus), daily length and weight gain, and condition factor decreased following 2 and 4 weeks of aqueous exposure to arsenic (159).…”
Section: Growthmentioning
confidence: 99%